THE ROLE OF ZIYARATS IN THE SUFI PILGRIMAGE PRACTICES OF FEMALE MURIDS IN INGUSHETIA - Albogacieva, Makka Sultan-Gireevna (History, Archeology and Ethnography of the Caucasus, 2026)
This article investigates the role of ziyarats (shrines dedicated to saints) within the Sufi pilgrimage practices of female murids in Ingushetia. The study aims to identify the specific characteristics of the religious experiences of these women, analyzing their motivations, ritual practices, and the social significance of their journeys. Central focus is placed on female religious activity associated with the cult of the awliya Kunta-Haji Kishiev, specifically the pilgrimages to shrines linked to his name. The research findings indicate that ziyarats play a vital role in the spiritual lives of female murids. Pilgrimage to these sacred sites is viewed as a means of spiritual purification, the atonement of sins, the attainment of barakat (divine blessing), and the establishment of a personal connection with Allah and the saints. Furthermore, these sites facilitate social interaction, the exchange of experience, and the strengthening of communal ties. Zikr and other ritual practices serve as platforms where women can express their religiosity, discuss life challenges, and receive support from fellow disciples. The analysis reveals that these women are driven by both personal and collective motivations. Personal ones include a need for spiritual growth, overcoming life’s hardships, and reinforcing faith. Collective ones include the maintenance of religious traditions, preservation of ancestral memory, and the promotion of social solidarity. The study concludes that for Sufi women, visiting ziyarats is a fundamental element of both religious and social life, providing a vital space for spiritual development, social engagement, and the reinforcement of cultural identity.
Keywords: Ingush people; Kunta-Haji; Qadiriyya Tariqa; Islam; Zikr; female murids; Sufi practices; Ziyarat; ritual